The Approach to Collaboration between the Community and the Police in Sustainable Crime Prevention: A Case Study of Nong Chok Metropolitan Police Station - โพธิ์เกษม ภนิดา; ชุติกุลวรนันท์ ผกากรอง; นุชอุดม เฉลิมพล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The study aims to enable the community and police to collaboratively establish sustainable guidelines or methods for crime prevention, so that the community becomes aware of and understands how to prevent crime within their area and can sustainably rely on themselves. This will allow the community and police to exchange information and access crime data quickly, accurately, consistently, and in a concrete network,and analyze the problems and obstacles in collaboration between the community and the police, including guidelines for sustainable crime prevention in the community. The present study used the qualitative methods and descriptive analysis and created and planned the research process by using a focus group and observation as the research instrumentation with reliance on documentary study based on gathered documents and targeted key data informants. The research found that both the community and police must be determined and sincere with each other in the performance of their duties as follows: 1. The police should regularly and continuously organize meetings between the community and the police to exchange up-to-date information about the crime situations or incidents in the area. 2. The police should regularly and continuously organize training and raise awareness for the public and communities about crime prevention methods. 3. The police should enhance their work capabilities by adopting modern technology in their operations and public services, using technology for surveillance and incident reporting. 4. Landscape improvement within the community, where the community, police, and relevant agencies collaborate to develop public spaces and the community to be safe consistently and continuously. 5. The police should carry out public relations and utilize technology as tools for surveillance and incident reporting. They should build networks between the police and the community to promote cooperation and encourage citizens to participate in taking responsibility for the community and society as a whole.